Numerical Analysis of Scuffing Risk in Involute Spur Gears Based on the Integral Temperature Criterion - Bozca, Mehmet; Lazovic, Tatjana; Sedak, Milos; Bodzas, Sandor (UNIV BELGRADE, FAC MECHANICAL ENGINEERING, 2026)
Gear scuffing is a major concern and a critical technical challenge in gear power transmission design. This paper reviews current research and practical approaches to understanding and preventing gear scuffing, drawing on both industrial experience, available standardization and academic studies. A dedicated MATLAB-based computational code is developed to systematically analyse the influence of geometrical, operational, and lubrication parameters on flash, mass, and integral temperatures. The results show that increasing the module, tooth number, and face width positively improve scaffing resistance, while higher torque, rotational speed, and oil temperature significantly increase scuffing risk, a failure mode that can substantially reduce gear service life. The applied model and the conducted analysis have shown that the obtained results can serve as a foundation for the development of future optimization models aimed at improving gear reliability and extending service life through appropriate parameter selection and design improvement.
Keywords: Gear failure; gear scuffing; integral temperature; mass temperature; flash temperature; ISO 6336-20; ISO 6336-21; ISO 10825; LUBRICANT FILM BREAKDOWN; MULTIOBJECTIVE OPTIMIZATION; SURFACE; TEETH; WEAR; Engineering